Singapore : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Singapore. (IMF Staff Country Reports; Country Report, 2019)
The 2019 Article IV Consultation with Singapore analyses that Singapore's growth is expected to continue to moderate as export momentum slows and growth drivers shift back to domestic demand. Risks to the near-term outlook are tilted to the downside and arise mainly from external sources. Over the medium term, modern services are expected to become increasingly important in driving growth. The report highlights that policies should be geared toward addressing the challenges to growth and inequality posed by shifts in the global economy, aging, and technological change, which could also promote external rebalancing. Policies have been aimed at boosting growth while promoting greater equity. The authorities are implementing measures to turn Singapore into a global innovation hub, redoubling efforts to boost labor productivity through investment in human, physical and organizational capital, and digitalization. Singapore is also emerging as a regional leader in fintech, supported by Monetary Authority of Singapore. Meanwhile, social policies are being updated, with the aim of raising wages and standards of living for lower-skilled Singaporeans.